Whole genome sequencing of Shigella sonnei through PulseNet Latin America and Caribbean: advancing global surveillance of foodborne illnesses - Baker, K S (2017)
Fil: Baker, K S. University of Liverpool, Department of Functional and Comparative Genomics, Liverpool, England, United Kingdom; Wellcome Trust Sanger Institute, Pathogen Variation Programme, Hinxton, England; Reino Unido.